Overview of Latin American studies on written feedback in graduate education (Praxis Educativa, 2024)
Research on the teaching of writing at postgraduate level values written feedback (WF) in this process. In order to understand this practice, we conducted a state of the art study to identify conceptualisations, categorisations, perceptions and textual and scriptural changes based on WF in communications in the field of Social and Human Sciences. Among the results, WF is conceived as an interactive practice, developed in diverse pedagogical-didactic contexts and conditioned by different factors. In addition, classifications of WF are identified, oriented towards different aspects involved in research writing. In terms of perceptions, the participants emphasise the formative nature of the practice. Finally, we found little research aimed at documenting the textual and scriptural changes resulting from WF. We conclude that research into this practice can contribute to the design of devices aimed at improving the teaching of writing at postgraduate level.
Keywords: retroalimentación, enseñanza de la escritura, escritura en posgrado